Does Cognitive Broadening Reduce Anger? - Summerell, Elizabeth; Harmon-Jones, Cindy; Kelley, Nicholas J.; Peterson, Carly K.; Krstanoska-Blazeska, Klimentina; Harmon-Jones, Eddie (Frontiers in Psychology, 2019)
Past theory and research have suggested that motivationally intense affective states narrow cognitive scope. Research has also suggested manipulations that broaden cognitive scope reduce responses to appetitive positive affective stimuli and disgusting stimuli, thus suggesting that cognitive broadening reduces motivational intensity. This led to the hypothesis that cognitive broadening would reduce the approach-motivated negative emotion of anger. Seven studies assessed the effect of cognitive broadening on reported trait anger, state anger, attitudes toward anger, attributions of anger to ambiguous pictures, and accessibility of aggressive words. Results from individual studies found mixed support for these predictions. A meta-analysis, however, suggested a small but significant effect on trait anger/aggression and attitudes toward anger across studies. These results may indicate that cognitive scope, as manipulated in these studies, has a small effect on anger-related responses. Discussion speculates on potential explanations of these findings, and their importance for informing future research.